Increasing trends of overweight and obesity in treatment-naive people living with HIV in Shenzhen from 2014 to 2020: an emerging health concern - Tianze Li; Liqin Sun; Yun He; Yang Zhou; Liumei Xu; Fang Zhao; Dongsheng Hu; Hui Wang; Hongzhou Lu; Jiaye Liu (Frontiers Media S.A., 2023)
BackgroundWith the early initiation of antiretroviral therapy (ART) in China, the demographics of treatment-naïve people living with HIV (PLWH) are moving closer to those of the general population, which is characterized by a gradual increase in metabolic indicators. However, the epidemic trends of overweight and obesity over the past decade in treatment-naïve PLWH ready to initiate ART have not yet been investigated.MethodsA cross-sectional study was conducted, including 12,135 consecutive treatment-naïve PLWH ready to initiate ART in Shenzhen, using data retrieved from the China National Free Antiretroviral Treatment Program database from 2014 to 2020. The chi-square test was used to examine the trends of overweight and obesity between age groups, and multivariate logistic regression was used to identify the association of overweight and obesity with hyperglycemia and dyslipidemia.ResultsDuring the 7-year study period, 12,135 treatment-naïve PLWH ready to initiate ART were included, among whom 1,837 (15.1%) were overweight and 388 (3.2%) were obese. The prevalence of overweight rose from 11.4 to 17.3% (Z = −4.58, P for trend <0.01) and that of obesity from 2.0% to 4.2% (Z = −6.45, P for trend <0.01) from 2014 to 2020. The annual prevalence of overweight was the highest in the age group of participants >35 years compared to prevalence in other age groups during the period 2014-2020. Compared with those who were not overweight or obese, PLWH who were overweight or obese were more likely to have hyperglycemia (aOR 1.84, 95% CI: 1.37-2.49 for overweight; aOR 2.68, 95% CI: 1.62-4.44 for obesity), higher ALT level (aOR 2.70, 95% CI: 2.33-3.13 for overweight; aOR 3.85, 95% CI: 2.93-5.05 for obesity), higher TG levels (aOR 1.89, 95% CI 1.63-2.19 for overweight; aOR 2.56, 95% CI 1.97-3.32 for obesity), and lower HDL levels (aOR 1.67, 95% CI 1.44-1.95 for overweight; aOR 2.06, 95% CI 1.54-2.77 for obesity).ConclusionThe prevalence of overweight and obesity in treatment-naive PLWH increased steadily from 2014 to 2020 in Shenzhen. Overweight and obese in treatment-naive PLWH ready to initiate ART were associated with dyslipidemia and hyperglycemia. Public health authorities should take proactive steps to address these issues by implementing targeted screening, intervention programs including lifestyle modifications, and integrated healthcare services.